EFFECTS OF PLANT GROWTH REGULATORS ON SHOOT MULTIPLICATION AND ROOT INDUCTION OF CASSAVA VARIETIES CULTURE IN VITRO - SUKMADJAJA, DEDEN; WIDHIASTUTI, HERNI (BIOTROPIA, 2024)
A study on propagation of three superior cassava Manihot esculenta( Crant) varieties i.e. Darul Hidayah, Malang-6 and Adira-4 through tissue culture technique was conducted at the Tissue Culture Lab of SEAMEO BIOTROP, Bogor. The objective of the experiment was to study effect of plant growth regulators on Manihot esculenta propagation, which can be used in cassava micropropagation protocol. Plant materials used were auxiliary shoots of a stem node. The experiment consisted of (i) shoot multiplication, (ii) roots induction, and (iii) acclimatization. The multiple shoot regeneration was observed by using Murashige & Skoog (MS) basal media supplemented with 0, 0.1, 1.0 and 5.0 mg/L of benzylaminopurine (BAP) combined with 0.0, 0.1 and 1.0mg/L of thidiazuron. The root induction was observed by using 0.1 and 1.0mg/L of IBA and NAA. The resulting plantlets were transplanted into plastic polybags containing soil mixed with organic fertilizer (1:1) covered with plastic sheets and transferred to a greenhouse. The result of the study showed that the highest number of shoots for Darul Hidayah, Malang-6 and Adira-4 varieties were 4.93 shoots treated with BAP 1 mg/L + thidiazuron 0.1 mg/L, 4.20 shoots at BAP media of 1 mg/L, and 7.20 shoots at the media of BAP 1 mg/L + thidiazuron 0.1 mg/L respectively. The highest number of nodes produced was 2.9 nodes for Darul Hidayah at BAP 5 mg/L, 5.13 nodes for Malang-6 at BAP 0.1 mg/L, and 6.18 nodes forAdira-4 at BAP 5mg/L + thidiazuron 1mg/L. The utilization of auxin IAA or NAA could induce and accelerate the growth of roots which finally could increase the success of acclimatization process. With an average of four multiplication factors of each culture period, the potency of each cassava shoot propagated through tissue culture could produce around 37 000 plants/year. Keywords:Manihot esculenta, shoot multiplication, root induction, BA, thidiazuron, IBA, NAA